Intra-increment Tracheid Length Variation in Branches and Roots of Blue Pine - Seth, M. K., Veena, Sadhna (Indian Forester, 1989)
Intra-increment tracheid length values have been observed to vary from earlywood to latewood in branches and around the circumference in roots of blue pine (Pinus wallichiana A.B. Jackson).